Preventive DC‐side decoupling: A system integrity protection scheme to limit the impact of DC faults in offshore multi‐terminal HVDC systems - Patrick Düllmann; Christopher Klein; Pascal Winter; Hendrik Köhler; Michael Steglich; Jan Teuwsen; Willem Leterme (IET Generation, Transmission & Distribution)
Abstract To create synergies between offshore wind integration and operational flexibility, interconnecting HVDC links to multi‐terminal networks is highly desired. However, its technical realisation remains a major challenge: In particular, it is crucial to prevent DC faults from leading to an intolerable loss of power infeed to the connected AC grids. To restrict this loss of power infeed, this paper proposes a concept for linear HVDC networks that is based on state‐of‐the‐art equipment only—that is, without dependence on DC circuit breakers. In this concept, the DC interconnection is preventively decoupled via DC high‐speed switches whenever the cumulative wind infeed exceeds the frequency containment reserve of the AC grid, but remains coupled at all other times. The decoupling is realised via controlling the coupling line current to zero through coordinated setpoint changes for the converters’ (VDC/P)‐droop controls. Both the decoupling sequence and the DC fault behaviour in decoupled state are validated via EMT simulations. In addition, limitations with regard to expandability are discussed. The proposed concept may not only limit the loss of infeed, but mitigates risks as a fall‐back level for more complex offshore (multi‐vendor) multi‐terminal HVDC topologies—and may thus accelerate their development at reasonable costs.